2003
DOI: 10.1258/jrsm.96.4.172
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term physical effects of exposure to CS spray

Abstract: SUMMARYCS gas (2-chlorobenzylidene malonitrile) is widely used in an incapacitant spray that causes intense lacrimation, blepharospasm and burning sensations in the throat and nose. Questions have been raised about its safety. We obtained information on short-term and long-term symptoms, and performed ear, nose and throat examinations and respirometry at 8-10 months, in 34 young adults who had been exposed to CS spray in a confined space during a confrontation with police. The group was subdivided into those w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 1 publication
2
11
0
1
Order By: Relevance
“…Coughing, wheezing, and dyspnea persisted for two years after short term exposure to CS in a previously well 21-year-old woman [ 4 ]. Among 34 young adults exposed to CS in a coach, 5 of them had respiratory symptoms, 2 had worsening of asthma, 2 had decreased exercise tolerance, and 1 complained of coughing fits after exercise at the examination done 8 to 10 months after the exposure [ 5 ]. Respiratory complaint rates between 26% and 44% among subjects exposed to tear gases in a regular basis (mean life-long exposure number 8.4 and the mean last 2 years exposure number 5.6) were compatible with the knowledge on the long term effects of CS in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Coughing, wheezing, and dyspnea persisted for two years after short term exposure to CS in a previously well 21-year-old woman [ 4 ]. Among 34 young adults exposed to CS in a coach, 5 of them had respiratory symptoms, 2 had worsening of asthma, 2 had decreased exercise tolerance, and 1 complained of coughing fits after exercise at the examination done 8 to 10 months after the exposure [ 5 ]. Respiratory complaint rates between 26% and 44% among subjects exposed to tear gases in a regular basis (mean life-long exposure number 8.4 and the mean last 2 years exposure number 5.6) were compatible with the knowledge on the long term effects of CS in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Karagama et al reported that out of 34 persons exposed to CS in a closed area 23 had respiratory complaints after one hour after the cessation of exposure. They followed the cases and showed that respiratory symptoms persisted for 10 months in 5 subjects [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In humans, the acute effects of DCA exposure are similar to the effects documented in animal studieseye redness, runny nose, cough, shortness of breath, phlegm, and chest pain (Karagama, Newton, and Newbegin 2003;Arbak et al 2014;Kearney et al 2014;Ilgaz et al 2019). However, few studies systematically and rigorously analyze their long-term health impacts.…”
Section: Health Effects Of Dcas In Human Studies and Incidental Ementioning
confidence: 86%
“…Many studies utilized people who had been incidentally exposed to DCAs, such as while attending a protest, and relied on individual recollections of health events. Still, the studies indicate that respiratory problems often occur in the days or weeks after DCA exposure and have the potential to linger for 10 months or longer (Arbak et al 2014;Dagli et al 2014;Karagama, Newton, and Newbegin 2003). These persistent symptoms included worsening of asthma, decreased exercise tolerance, and coughing.…”
Section: Health Effects Of Dcas In Human Studies and Incidental Ementioning
confidence: 99%
“…TRPA1 plays an important role in allergen‐induced asthma 54 . One of the long‐term severe consequences of tear gas exposure is asthma 201 . Tear gas sprays generate particulate matter.…”
Section: Pulmonary Chemical Threat Agentsmentioning
confidence: 99%